Guias didáticos - propostas inovadoras: volume 3 - Bailoni, Ludmila Fratucci; Gomes Junior, Estevão Conceição; Yoshi, Cássia Valéria Hungaro; Niwa, Andressa Megumi; Magalhães, Leandro Henrique; Rodrigues, Matheus Moreto Guisso; Cavariani, Marília Martins (Livros Editora UniFil; Livros Editora Unifil, 2025)
Acesse o e-book  aqui